2018
DOI: 10.1007/s00261-018-1763-1
|View full text |Cite
|
Sign up to set email alerts
|

Textural analysis on contrast-enhanced CT in pancreatic neuroendocrine neoplasms: association with WHO grade

Abstract: Our data indicated that texture parameters have potential in grading PNENs, in particular in differentiating PNEC G3 from PNETs G1/G2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 30 publications
2
46
1
Order By: Relevance
“…Texture parameters, such as entropy and kurtosis, show good performance in differentiating benign from malignant tumors (16, 17). Several studies also indicate that texture features are good predictors of tumor grades (18, 19). However, few studies have shown the role of texture features in PTs grading.…”
Section: Discussionmentioning
confidence: 99%
“…Texture parameters, such as entropy and kurtosis, show good performance in differentiating benign from malignant tumors (16, 17). Several studies also indicate that texture features are good predictors of tumor grades (18, 19). However, few studies have shown the role of texture features in PTs grading.…”
Section: Discussionmentioning
confidence: 99%
“…Some CT and MR findings are effective in predicting the aggressiveness and grade of the tumor, for example as arterial phase hypovascularization, major vessel invasion, or size [ 25 , 26 , 27 ]. In particular, many studies in the literature have described the hypoenhancement of p-NETs tumors as a strong predictor of a high-grade tumor [ 28 , 29 , 30 , 31 ]. Our study reported analogous results on this latter parameter, with the hypovascularization of liver metastases being one of the best LTB descriptors in the prediction of high tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between entropy values and different tumor grades of p-NETs has already been a matter of study [ 26 , 30 , 32 , 33 ]. In these studies, entropy was found to be an excellent predictor of the tumor grade when comparing G1 vs. G2–3 [ 26 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the abdominal features of the pancreas and the variation in the volume and shape of the pancreas presented by the interpatient [31,32], this paper manually drew the ROI of the pancreas. First, the CT sequence images in DICOM format were converted into JPG format and then imported into LabelMe software where two clinicians (Wei Han has 21 years and Yilidan Reheman has 3 years of clinical experience in abdominal CT) manually drew ROIs along the edge of the pancreas [33]. To improve model generalization ability, we selected 3 cross-sectional images of plain CT scans with significant features from each CT sequence on average [27,34,35].…”
Section: Pancreas Segmentationmentioning
confidence: 99%